2006
DOI: 10.1080/00016480500390345
|View full text |Cite
|
Sign up to set email alerts
|

Malleus head fixation: histopathology revisited

Abstract: Three types of acquired malleus head fixation were defined in accordance with the surgical and histopathological findings. Histologically, the first type presented with normal bone tissue, the second was characterized by non-tympanosclerotic bone remodeling and the third presented with a localized tympanosclerotic focus in the tympanic cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Isolated fixation of the malleus is the least common form of ossicular chain fixation, 5 and it occurs in 0.4% to 1.6% of all cases of CHL and is often unilateral. [6][7][8][9] Audiometric evaluation in the patient demonstrated persistent bilateral CHL greater than 30 to 35 dB after tympanostomy tube placement. In otitis media-related CHL, the expected level of hearing loss is less than 35 dB HL, which helped raise suspicion for ossicular chain abnormalities.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Isolated fixation of the malleus is the least common form of ossicular chain fixation, 5 and it occurs in 0.4% to 1.6% of all cases of CHL and is often unilateral. [6][7][8][9] Audiometric evaluation in the patient demonstrated persistent bilateral CHL greater than 30 to 35 dB after tympanostomy tube placement. In otitis media-related CHL, the expected level of hearing loss is less than 35 dB HL, which helped raise suspicion for ossicular chain abnormalities.…”
Section: Discussionmentioning
confidence: 86%
“…Stewart and Downs reviewed congenital CHL and found that only 3 patients of 54 had isolated, nonsyndromic middle ear abnormalities. Isolated fixation of the malleus is the least common form of ossicular chain fixation, and it occurs in 0.4% to 1.6% of all cases of CHL and is often unilateral …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, osteosclerosis reportedly occurs in cholesteatoma as a result of chronic inflammation 42 ; activin A reportedly affects osteosclerosis in fibrodysplasia ossificans progressiva and heterotopic ossifications 43,44 . In the present study, the scRNA-seq analysis revealed the upregulation of extracellular matrix-related genes in cholesteatoma fibroblasts, including collagen proteins and proteoglycans, which are related to osteogenesis, mineral deposition, and bone remodeling 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Although several techniques have been described for reconstruction of the sound conduction mechanism, surgical management of tympanosclerosis in cases of incudomalleolar fixation remains controversial. There are also controversies regarding the choice of surgical technique 9 11 …”
Section: Discussionmentioning
confidence: 99%
“…Various surgical techniques have been described and utilised; however, the option of surgery and the choice of surgical technique remain controversial 9 11 . A variety of reconstruction materials have been used for ossiculoplasty, including homograft ossicles or cartilage, partial or total ossicular reconstruction prostheses, and, more recently, bone cements.…”
Section: Introductionmentioning
confidence: 99%